Immune-related adverse events of biological immunotherapies used in COVID-19 - Daniela Baracaldo-Santamaría; Giovanna María Barros-Arias; Felipe Hernández-Guerrero; Alejandra De-; Carlos-Alberto Ca; Carlos-Alberto Ca (Frontiers Media S.A., 2022)
The use of biological immunotherapeutic drugs is one of the options currently being evaluated and employed to manage COVID-19, specifically monoclonal antibodies, which have shown benefit by regulating the excessive immune response seen in patients with severe infection, known as a cytokine storm. Tocilizumab has received particular importance for this clinical application, as has sarilumab. Both drugs share a substantial similarity in terms of pharmacodynamics, being inhibitors of the interleukin six receptor (IL-6Rα). Furthermore, sotrovimab, a neutralizing anti-SARS CoV-2 antibody, has gained the attention of the scientific community since it has recently been authorized under certain circumstances, positioning itself as a new therapeutic alternative in development. However, despite their clinical benefit, biological immunotherapies have the potential to generate life-threatening immune-related adverse events. Therefore it is essential to review their incidence, mechanism, and risk factors. This review aims to provide a comprehensive understanding of the safety of the biological immunotherapeutic drugs currently recommended for the treatment of COVID-19, provide a review of the known immune-mediated adverse events and explore the potential immune-related mechanisms of other adverse reactions.